Victorian Alpine Plot Network (Alpine Summit Plots): Plot Details - Spatial Coordinates for Lowland-to-highland Roadside Transects Walking Track Data, South-East Highlands, Australia - University of Melbourne; John Morgan; Ary Hoffmann (TERN Australia, 2018)
This Victorian Alpine Plot Network Road Transects Walking Track Data Package comprises spatial data for Lowland-to-highland Roadside Walking Track Transects in the South-East Highlands, Australia. Plots are numbered chronologically along the transects. The transects follow three walking tracks in the Victorian Alps. Each track is divided into 200 m long, 3-4 m wide plots. The Alpine Summit plots study, which commenced in 2001, forms part of the collection of data packages by the Victorian Alpine Plot Network. A synopsis of related data packages which have been collected as part of the Victorian Alpine Plot Network’s full program is provided at http://www.ltern.org.au/index.php/ltern-plot-networks/victorian-alpine.